2009
DOI: 10.1186/1475-9276-8-44
|View full text |Cite
|
Sign up to set email alerts
|

The influence of insurance status on waiting times in German acute care hospitals: an empirical analysis of new data

Abstract: BackgroundThere is an ongoing debate in Germany about the assumption that patients with private health insurance (PHI) benefit from better access to medical care, including shorter waiting times (Lüngen et al. 2008), compared to patients with statutory health insurance (SHI).ProblemExisting analyses of the determinants for waiting times in Germany are a) based on patient self-reports and b) do not cover the inpatient sector. This paper aims to fill both gaps by (i) generating new primary data and (ii) analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…In Deutschland wurde bisher jedoch kaum untersucht, ob neben dieser Statuszugehörigkeit auch die Zugehörigkeit zu einer Gesetzlichen (GKV) beziehungsweise Privaten Krankenversicherung (PKV) einen bedeutsamen Einfluss auf den Zugang zur gesundheitlichen Versorgung und auf den Gesundheitszustand hat. Die diesbezüglich vorhandenen Forschungsergebnisse sind zudem sehr verstreut, und ein zusammenfassender Überblick über diese Arbeiten liegt bisher noch nicht vor [7,8,9,10,11].…”
Section: Originalien Und üBersichtenunclassified
“…In Deutschland wurde bisher jedoch kaum untersucht, ob neben dieser Statuszugehörigkeit auch die Zugehörigkeit zu einer Gesetzlichen (GKV) beziehungsweise Privaten Krankenversicherung (PKV) einen bedeutsamen Einfluss auf den Zugang zur gesundheitlichen Versorgung und auf den Gesundheitszustand hat. Die diesbezüglich vorhandenen Forschungsergebnisse sind zudem sehr verstreut, und ein zusammenfassender Überblick über diese Arbeiten liegt bisher noch nicht vor [7,8,9,10,11].…”
Section: Originalien Und üBersichtenunclassified
“…Although helpful in getting a general sense of access, heterogeneity in wait times can be obscured. For example, studies have shown that privately insured patients have better access to physicians than publicly insured patients do (Kuchinke, Sauerland, & Wubker, 2009, found this to be the case in Germany for hospital admissions; Czypionka, Kraus, Riedel, & Rohrling, 2007, in Austria for elective surgery; MedPAC, 2017, in the United States for routine care). This is conceivably the rational choice given that private providers may be trying to maximize profit.…”
mentioning
confidence: 99%
“…Apparently, there is only little evidence for the existence of a so called two-tier medicine -at least with respect to our dataset. However, in contrast to Kuchinke, Sauerland & Wübker (2009), who analyzed whether hospitals discriminate patients in waiting times by their insurance status, we aim at a more competition policy related issue. That is, we analyze the impact of the degree of competition between hospitals on the probability that a hospital inquires a patients' insurance status.…”
Section: Datamentioning
confidence: 99%